Seasonal Change in Home Blood Pressure Monitoring Is Associated With Renal Outcome and Mortality in Patients With Chronic Kidney Disease - See, Chun Yin; Tseng, Chien-Tzu; Lin, Wei-Ren; Chao, Jo-Yen; Kuo, Te-Hui; Wang, Ming-Cheng (Frontiers in Medicine, 2021)
Background: Blood pressure (BP) variation may result in poor cardiovascular and renal outcomes. We investigated the pattern of seasonal BP change and its association with outcomes in patients with chronic kidney disease (CKD) living in southern Taiwan. Method: We conducted a retrospective analysis of a prospective observational cohort consisting of outpatients with CKD for the period between December 2014 and December 2019. These patients were grouped according to the pattern of seasonal BP variation, namely, consistently higher average systolic BP (>8 mmHg) in summertime than wintertime (group A), consistently lower average systolic BP (>8 mmHg) in summertime than wintertime (group B), large seasonal BP variation (>8 mmHg) but without a specific trend (group C), and little fluctuation in seasonal BP (<8mmHg; group D). The study endpoints were doubling of baseline serum creatinine, initiation of dialysis, kidney transplantation, or death. Result: We analyzed 507 eligible patients, of whom 17.2% exhibited consistent BP elevation in the wintertime. For 56.8% of the patients, regular home BP measurement data were available. Compared with those in the other three groups, patients with consistent BP elevation in the wintertime were older and had a higher prevalence of diabetic nephropathy, lower prevalence of statin use, higher level of baseline serum creatinine, lower levels of estimated glomerular filtration rate, and poorer outcomes. Multiple logistic regression analysis indicated that consistent home BP elevation in the wintertime in those with CKD was significantly associated with poorer outcomes (i.e., serum creatinine doubling, dialysis, transplantation, or death) after adjustment for various confounding factors. Conclusion: Home BP monitoring is critical, and the relevant data serve as a more accurate outcome predictor than office monitoring. Consistently elevated home-measured BP elevation in the wintertime in patients with CKD was associated with a poorer composite patient outcome.